(untitled) (Global Journal of Human-Social Science, 2022)
This article aims to understand the role that digital media play in the culture wars framework To this end a theoretical discussion of the notion of digital media and culture wars is conducted pointing to impactful aspects of both which will be perceived in a qualitative case study - the 2021 Wi Spa Confrontation - comparing Fox News The Washington Post and The Guardian as well as general positionings on Twitter The conclusion is that digital media proves itself to be a central battleground in the conflict between discourses and meanings that are central to the culture wars with the deeper moral debate surfacing only briefly fueling the apparent dispute without dissolving the polarization